2013
DOI: 10.1227/neu.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for Refractory Epilepsy in Childhood

Abstract: Reoperation is particularly beneficial for selected children with refractory epilepsy associated with cortical dysplasia that did not respond to an initial limited and/or early resection but achieved seizure freedom after extensive procedures. When indicated, reoperation should be performed at the youngest possible age to profit from higher functional plasticity in compensating for neurological deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 30 publications
7
69
0
7
Order By: Relevance
“…Although this study was not designed to be a pediatric study and that our normal control database mainly consists of adults, out of the 10 patients in whom we discussed in detail the relevance of the unresected MAP+ regions, 7 were children, ranging from 9 to 15 years of age. As indicated by previous studies, current approaches in pediatric epilepsy surgery reflected a preference for noninvasive modalities, especially improved neuroimaging techniques, to invasive evaluation in the planning of resections [7, 21, 22]. Overall, our findings suggest MAP can be particularly helpful in pediatric patients with FCD-associated epilepsies.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although this study was not designed to be a pediatric study and that our normal control database mainly consists of adults, out of the 10 patients in whom we discussed in detail the relevance of the unresected MAP+ regions, 7 were children, ranging from 9 to 15 years of age. As indicated by previous studies, current approaches in pediatric epilepsy surgery reflected a preference for noninvasive modalities, especially improved neuroimaging techniques, to invasive evaluation in the planning of resections [7, 21, 22]. Overall, our findings suggest MAP can be particularly helpful in pediatric patients with FCD-associated epilepsies.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, new challenges present such as breach effect from the postoperative skull defects, which can severely distort scalp-EEG localization of epileptic events. At this moment, studies reported seizure-free rates for reoperation vary quite considerably from 9.5 to 57 % with considerable room for improvement [5, 7]. In devising the reoperation plan for the failed patients, any novel noninvasive technique which can add to the evaluation test battery is highly valued.…”
Section: Introductionmentioning
confidence: 99%
“…While reoperation for intractable epilepsy has been shown to result in favorable seizure freedom in 19-57 %, there have been few studies looking specifically at surgical outcomes following reoperation for pediatric patients with FCD [2,4,8,11,25,28]. Two recent studies have reported achieving seizure freedom in 61 and 50 % upon further surgeries in pediatric and mixed aged patients with intractable epilepsy secondary to FCD; however, it is difficult to correlate such findings as each cohort is small and heterogeneous [13,21]. Moreover, further reoperations lead to greater chance of post-surgical neurological complications and surgical site infections (SSIs) [2,16].…”
Section: Discussionmentioning
confidence: 99%
“…We also included children who had undergone previous resective surgery but had ongoing seizures, because repeat surgery is still a feasible option for these individuals. 8 The following data were collected: demographic (sex, age at onset of epilepsy, and at monitoring), epilepsy details (seizure types and current number of semiologies at onset of clinical seizures, electroclinical syndrome, etiology, seizure frequency, history of neonatal seizures), presence of intellectual disability, prior and current treatments (number of antiepileptic drugs currently on and number failed for lack of efficacy, current/ prior ketogenic diet use, vagus nerve stimulation, prior epilepsy surgery), outpatient EEG results (presence of generalized or focal slowing, presence and localization of interictal dischargeesingle focus, two foci, hemispheric, multifocal, generalized, generalized and focal, hypsarrhythmia), and neuroimaging results (presence of, type, and location of abnormalities using an epilepsy protocol MRI). In our center, this MRI includes the following sequences: axial and coronal T1; axial T2; coronal T2 fluidattenuated inversion recovery; sagittal T1 fluid-attenuated inversion recovery; axial gradient echo; axial diffusion-weighted imaging; sagittal, axial, and coronal magnetization-prepared rapid gradient echo; and sagittal, axial, and coronal double inversion recovery.…”
Section: Methodsmentioning
confidence: 99%
“…The seven variables reaching statistical significance on univariable analysis were entered into a logistic regression (1), mesial temporal lobe epilepsy with hippocampal sclerosis (8), West syndrome (6), Lennox Gastaut (4), Rasmussen (2), and Ohtahara (1).…”
Section: Multivariable Analysismentioning
confidence: 99%